Controls on Neogene carbonate facies and stratigraphic architecture of an isolated carbonate platform – the Caribbean island of Bonaire. (June 2018) - Laya, Juan Carlos; Sulaica, Jonathan; Teoh, Chia Pei; Whitaker, Fiona; Gabellone, Tatyana; Tucker, Maurice E.; Tesch, Philipp; Miller, Brent; Prince, Kieron; Izaguirre, Ingrid
Abstract: The Neogene carbonate succession on the island of Bonaire (Netherland Antilles) shows complex geometries associated with a sequence of depositional and erosional events which reflects the history of this isolated platform and the interaction between eustasy and tectonics. Three major episodes of carbonate platform deposition are defined which show contrasting depositional styles: 1) aggradational platform (Lower-Middle Miocene) with sediments showing a fining-upward trend from mixed coral rudstone to medium-grained coralgal grain/packstone, partly dolomitized and tilted by tectonic deformation; 2) progradational platform (Upper Miocene-Pliocene) which is formed of several shallowing-upward prograding units mainly composed of reworked red algal grain/packstone, with significant dolomitization, passing upward to shoreline and aeolian deposits formed of cor-algal grain/packstone and large benthic foraminifera grainstone, and 3) flat-topped platform (Pleistocene) with a reefal framework composed of a rich variety of corals in a bioclastic pack/wackestone matrix. These platform episodes exhibit contrasting stacking patterns and are separated by erosional unconformities. Overprinting this depositional succession is a series of Quaternary near-horizontal shoreline erosional terraces and vertical cliffs which have been cut into the island stratigraphy and complicate the stratal field relationships. However, this terrace morphology clearly does not represent depositional episodes, as has been suggested before. The internal architecture of each of the three carbonate platform reflects of the dynamics of sedimentation with allogenic controls. The latter relate to major oceanographic and tectonic events in the region, including changing ocean circulation as a result of the closure of the Panama isthmus, and Caribbean plate dynamics that affected sea-floor and island topography. The Bonaire succession provides a model for understanding and predicting isolated carbonate platform development, as well as architecture, facies and potential diagenetic changes, in an active tectonic setting. Highlights: Isolated carbonate platforms respond to allogenic controls by changing depositional styles. Allogenic factors are the dominant controls on island-scale depositional events. Island terrace morphology has weak impact on depositional events interpretations. Internal architecture reflects the dynamics of sedimentation in complex islands.